Proceedings of the 2010 Spring Simulation Multiconference 2010
DOI: 10.1145/1878537.1878653
|View full text |Cite
|
Sign up to set email alerts
|

Gtna

Abstract: Concise and reliable graph-theoretic analysis of complex networks today is a cumbersome task, consisting essentially of the adaptation of intricate libraries for each specific problem instance. The growing number of complex metrics that have been proposed in the last years, which mainly gain significance due to the increasing computational capabilities at hand, have led to important new insights in the field. However, they have solely been implemented as single algorithms, each specialized for the purpose of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…However, in our scheme, we select landmark intermediate nodes through public fundraising for CBS (in Section 3). We use GTNA 8 to map the network topology, and there is a random value r $r$ for each node in the obtained graph. The random value r $r$ will determine whether to join the CBS and which Community to enter in the case to join the CBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our scheme, we select landmark intermediate nodes through public fundraising for CBS (in Section 3). We use GTNA 8 to map the network topology, and there is a random value r $r$ for each node in the obtained graph. The random value r $r$ will determine whether to join the CBS and which Community to enter in the case to join the CBS.…”
Section: Methodsmentioning
confidence: 99%
“…A typical solution is the Payment Channel Network (PCN), 1,4–6 which enables plenty of payments without requiring to access the blockchain, other than to initialize and close each channel. Lightning network 7,8 and Raiden network are the offline payment networks built by Bitcoin and Ethereum, respectively with the help of PCN. The key insight of PCN is to put the transaction into the off‐chain network and employ the routing algorithm to find the appropriate payment path for the transaction.…”
Section: Introductionmentioning
confidence: 99%
“…We implemented all models in GTNA, a framework for the graph-theoretic analysis of network snapshots [22]2. We generated 20 instances for each model, parameter set, and size and averaged their graph-theoretic properties.…”
Section: A Implementation Of Models and Analysismentioning
confidence: 99%
“…To analyze different graph theoretical properties of our constructed city mesh networks we used the Graph-Theoretic Network Analyzer (GTNA) (Schiller, Bradler, Schweizer, Mühlhäuser, & Strufe, 2010). We found that networks constructed using all routers would show good performance and high resiliency to node failures.…”
Section: Preliminary Evaluationmentioning
confidence: 99%